Phytochemical constituents and antioxidant activities of two Nigerian retailed polyherbal formulations - Okagu, I.U.; Ndefo, J.C.; Chibuogwu, C.C. (Journal of Drug Delivery and Therapeutics, 2019)
Oxidative stress has been implicated in many neurodegenerative diseases, cancers and even ageing processes. This warrants that dietary antioxidants are needed to complement endogenous antioxidant defence system and prevent the development of these chronic diseases. In this study, the phytochemical constituents and antioxidant activities of two retailed Nigerian polyherbal formulations (DRHM® and GCHM®) were evaluated in vitro using DPPH radical scavenging activity, total antioxidant capacity (TAC) and ferric reducing antioxidant power (FRAP) models. Aside for saponins, glycosides, anthraquinones and anthocyanins which were higher in DRHM and alkaloids which were higher in GCHM, there was no significant (p < 0.05) difference among the amount of other phytochemicals detected in the two polyherbal formulations. The DPPH radical scavenging effect exhibited by DRHM (EC50 = 1.62x106 µg/ml) was significantly (p < 0.05) higher than GCHM (EC50 = 574.5 µg/ml) but that of ascorbic acid (EC50 = 10.58 µg/ml) was significantly (p < 0.05) higher than both DRHM and GCHM. Similarly, GCHM (EC50 = 0.005414 µg/ml) had higher FRAP than DRHM (EC50 = 5.302 µg/ml). However, the TAC of GCHM (EC50 = 1675 µg/ml) was significantly (p < 0.05) higher than that of DRHM (EC50 = 6.101 µg/ml). These findings suggest that the two polyherbal formulations possess appreciable antioxidant potentials which could be attributed to the presence of phytochemicals with antioxidant potentials. The polyherbal formulations can further be explored for possible harnessing of their antioxidant effect in prevention and management of oxidative stress-related disorders and ageing process.Keywords: polyherbal formulations, phytochemicals, antioxidants, DPPH, FRAP, TAC